Novel TBC1D8B Variant in a 6-Month-Old Boy With Steroid-Sensitive Nephrotic Syndrome: A Case Report - Hou, Ling; Yin, Lu; Wu, Yubin; Zhao, Chengguang; Du, Yue (Frontiers in Pediatrics, 2021)
A structural abnormality or dysfunction of podocytes is the major cause of nephrotic syndrome (NS). The TBC1D8B protein interacts with nephrin, a podocyte slit diaphragm protein, regulates vesicle transport, and functions in the pathogenesis of NS. We report a novel potentially pathogenic variant in the TBC1D8B gene in a 6-month-old boy with NS. A 6-month-old boy was admitted to the hospital because of edema and fever. Our systematic examination led to a diagnosis of NS. Because of the early age of onset, we performed trio whole-exome sequencing of him and his parents. The results showed a new potentially pathogenic variant in the TBC1D8B gene on the X chromosome, c.2717A>G (p.His906Arg). After routine glucocorticoid therapy, his urine protein turned negative, indicating steroid-sensitive NS. The new TBC1D8B variant identified here, c.2717A>G (p.His906Arg), may be associated with early-onset NS in children. Although NS due to pathogenic variants in this gene is more commonly steroid-resistant, our patient had steroid-sensitive NS.